Simulation analysis of steam gasification of petroleum coke with CaO. (17th December 2018) - Tian, Wei; Yan, Fusheng; Liang, Rongzhen
Abstract: The work deals with the effect of calcium oxide adsorption on the production of hydrogen and methane in steam gasification of petroleum coke using Aspen Plus process simulator. The prediction accuracy of the proposed model is verified by comparing with the existing experimental results. The effects of water vapor flux, the mass ratio of calcium oxide to petroleum coke, pressure, temperature on hydrogen or methane gasification from petroleum coke steam are studied. The production of hydrogen from petroleum coke gasification requires a low temperature and low pressure environment, while increasing the flow of water vapor is beneficial to the production of hydrogen. Maximum H2 volume fraction of 87.3% is obtained at a temperature of 600 °C, a pressure of 0.1 MPa, the mass of steam to petroleum coke is 1, and the mass of CaO to petroleum coke is 3. The H2 and CO2 volume fractions are found to be increased and decreased by 20% and 27.8% respectively, when compared with the corresponding non-CaO case. The production of methane from petroleum coke gasification requires a low temperature and high pressure environment, while decreasing the flow of water vapor is beneficial to the production of methane. Maximum CH4 volume fraction of 63% is obtained at a temperature of 600 °C, a pressure of 1 MPa, the mass of steam to petroleum coke is 1, and the mass of CaO to petroleum coke is 1. The CH4 and CO2 volume fractions are found to be increased and decreased by 14.4% and 21% respectively, when compared with the corresponding non-CaO case.